2021
DOI: 10.3390/nu14010121
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Association of Food Source with Food Insecurity, Dietary Diversity and Body Mass Index in Western Kenya

Abstract: The triple burden of malnutrition in many low- and middle-income countries (LMICs) is partly a result of changing food environments and a shift from traditional diets to high-calorie Western-style diets. Exploring the relationship between food sources and food- and nutrition-related outcomes is important to understanding how changes in food environments may affect nutrition in LMICs. This study examined associations of household food source with household food insecurity, individual dietary diversity and indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…12 Considering the very high number of households in our sample identified as being food insecure, further consideration should be given to the utility of these measures when used within LMICs, like Kenya. However, the rate of households identified in this study as being food insecure (89%) is comparable to other food insecurity measures in Kenya, which range from 72.3% 25 to 84% 26 being moderately or severely food insecure.…”
Section: Discussionsupporting
confidence: 66%
“…12 Considering the very high number of households in our sample identified as being food insecure, further consideration should be given to the utility of these measures when used within LMICs, like Kenya. However, the rate of households identified in this study as being food insecure (89%) is comparable to other food insecurity measures in Kenya, which range from 72.3% 25 to 84% 26 being moderately or severely food insecure.…”
Section: Discussionsupporting
confidence: 66%
“…In Kenya, the study of dietary diversity is dominated by research on the relationship between smallholder agricultural production and dietary diversity in rural areas (for example, [29][30][31][32]). Less attention has been given to dietary diversity in urbanising Kenya, although that is beginning to change [33].…”
Section: Introductionmentioning
confidence: 99%
“…Kimani-Murage and colleagues in two separate papers [34,35] showed that slum households are not only highly vulnerable to food insecurity but also experience a double burden of malnutrition with high levels of chronic child malnutrition co-existing with high levels of maternal obesity. A recent household survey in the secondary city of Kisumu showed a clear link between poverty and dietary deprivation [32]. Another study of three small towns in central Kenya found significant negative shifts in dietary composition accompanying supermarket shopping with increased consumption of highly processed foods [33,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The land terrain, socioeconomic and food retail characteristics of both control and intervention areas were delineated as similar as possible ( 19 ). This secondary analysis has used baseline cross-sectional data from both the intervention and control areas as applied in a related analysis ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Achievement of minimum dietary diversity was coded as a binary no/yes variable with minimum dietary diversity implying a dietary diversity score of 5 and above. This approach has been used in recent similar studies and a previous analysis using this dataset ( 20 , 28 ).…”
Section: Methodsmentioning
confidence: 99%